Family matters: parental entrepreneurial background and intentions - Haj Youssef, Moustafa (2026)
Purpose We investigate how family background shapes entrepreneurial intentions (EI) among employed adults in the Arab world. While much of the EI literature focuses on students and nascent entrepreneurs, we examine how parental entrepreneurship influences intention formation in adulthood, accounting for mediating psychological mechanisms, contextual moderators, and gendered dynamics. Design/methodology/approach We hypothesise that entrepreneurial self-efficacy mediates the relationship between parental entrepreneurship and EI, and that perceived entrepreneurial culture moderates this pathway. Using primary survey data from 4,167 employees across six Arab MENA countries, we apply regressions, mediation, and moderated mediation analyses to test these hypotheses. Findings Parental entrepreneurship is positively associated with EI, but this effect is concentrated among men. Self-efficacy mediates the intergenerational link, again primarily for men, and the mediation is strongest when entrepreneurial culture is perceived as less supportive. For women, by contrast, the direct effect of parental entrepreneurship on entrepreneurial intention is statistically insignificant, and the mediating role of self-efficacy is weak and largely unsupported. Originality/value We advance the EI literature by moving beyond student populations to focus on employed adults in a region where entrepreneurship is both family-embedded and institutionally constrained. It demonstrates that intergenerational transmission of entrepreneurship is conditional on both gender and cultural context, offering theoretical insights into how family, culture, and efficacy jointly shape entrepreneurial aspirations, while also offering practical guidance for policies promoting inclusive entrepreneurship in the Arab MENA region.